MODERN DIGITAL TOOLS FOR PROGECT PRESENTATION: TRANSFORMATION OF GRAPHICS AND COLOR - Sobko, Yulia (Sworld-Us Conference proceedings, 2025)
The article examines modern digital tools for presenting architectural and design projects that transform traditional approaches to visualization, graphics, and color. The capabilities of software packages for 3D visualization and rendering are analyzed,